Nurses' knowledge, beliefs and practices regarding the screening and treatment of postpartum depression in maternal and child health clinics: A cross-sectional survey - San, Kang Pei; Mohamed, Mohazmi; Ng, Yong Muh; Liew, Su May (Academy of Family Physicians of Malaysia, 2019)
Background: Postpartum depression (PPD) affects 10-15% of women worldwide, and screening is recommended by clinical guidelines. In Malaysia, nurses in maternal and child health (MCH) clinics provide postpartum care. Aim: To determine nurses’ level of knowledge, beliefs and practices regarding PPD and factors associated with screening practices. Methods: A cross-sectional study using universal sampling was conducted on nurses from seven government MCH clinics in Malaysia. Data was collected from March until April 2016 through a self-reported questionnaire. Univariate and multivariate analyses were performed to identify factors associated with having ever performed PPD screening. Results: Of the 108 nurses, 55.6% scored above the median total knowledge score (17 out of 24 points). Despite a high proportion of nurses believing that they were responsible for PPD screening (72.2%), counselling depressed mothers (72.2%) and referring mothers for further treatment (87.0%), only 64.8% and 51.9% were confident in recognizing PPD and counselling depressed mothers, respectively. Only 25.9% had ever practiced PPD screening, which was associated with beliefs concerning screening taking too much time (adjusted odds ratio [AOR]=0.13, 95% confidence interval [CI]= 0.02–0.74, P=0.022) and that screening is their responsibility (AOR=14.12, 95%CI=1.65-120.75, P=0.016). Conclusion: More than half of the nurses scored above the median total knowledge score and had positive beliefs towards PPD screening. However, PPD screening practices were poor, and this outcome was associated with their beliefs regarding time and responsibility. © 2019 Malaysian Family Physician. All rights reserved.